ANALYSIS OF TRENDS IN THE DEVELOPMENT OF SHARIA CAPITAL MARKET PRACTICES USING BIBLIOMETRIC ANALYSIS - M. Fauzan; Ananda Anugrah Nasution; Rendy Syaid Abdullah (International Journal of Social Science, Educational, Economics, Agriculture Research and Technology (IJSET), 2025)
The problem of this research is:lack of exploration of the long-term impact of implementing new technologies such as cryptocurrency in Islamic capital markets, which is still not widely discussed in the current literature. The purpose of this study is to analyze publication patterns, collaboration networks between researchers, and developments in topics related to Islamic capital markets. From a theoretical perspective, there are different views regarding the effectiveness of implementing Islamic principles in responding to the ever-changing dynamics of the global market. Purpose. Data were obtained from Crossref Search for five years (2019-2024) with the keyword "Sharia Capital Market Practices". Analyzed using bibliometrics with Harzing's Publish or Perish (PoP) and visualized using VOSviewer. The findings show that the development trend of Islamic capital market practices during 2019-2024 shows a shift in focus from fundamental aspects such as financial performance and capital structure of Islamic banking towards greater attention to technological innovation and social change. Initially, research concentrated heavily on the analysis of profitability, liquidity, and capital structure in Islamic banking. However, with the COVID-19 pandemic, topics such as the post-pandemic economic impact have begun to emerge, along with issues related to investor behavior and investment returns. In the following period, especially 2022-2023, there is increasing interest in new technologies such as cryptocurrency and metaverse, indicating that the Islamic capital market is adapting to the digital era. The implication of this finding is that the Islamic capital market needs to continue to develop innovative strategies to face global challenges and utilize digital technology to strengthen its competitiveness. Going forward, research and policies that focus on the application of new technologies, strengthening the Islamic legal infrastructure, and understanding investor behavior are important to support the growth of the Islamic capital market.